Analyzing the Role of Research and Development in Policy Making in the Pussenkav - Adzan Marjohan Nasution; Rini Mulyani Sari (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2024)
The Cavalry Weapons Center (Pussenkav) of the Indonesian Army Military Command is a special staff of the Kasad in the areas of weapons development and training, military horse training, research and development, and organic training to support the army's main missions. The purpose of this study was to examine the influence of research and development on policymaking in the Pussenkav unit. This study uses a qualitative method with a phenomenological perspective. Purposive sampling was employed by the study's resource personnel, who totaled thirteen. Data collected from interviews, documentation studies, and literature reviews were triangulated and analyzed using Miles and Huberman's theoretical literature. The findings revealed that Pussenkav's Research and Development Division was not involved in the full policy process, resulting in policies that were both irrelevant and ineffective in solving problems in the Cavalry Unit, Pussenkav's operational management was not properly carried out, and many departments still do not understand each other's processes, tasks, and obligations, and Pussenkav's R&D products or results have not attracted the attention of the leadership in policy development.